Radiomics analysis for prediction and classification of submucosal tumors based on gastrointestinal endoscopic ultrasonography - Hui Zhou; Guoliang Wei; Junke Wu (DEN Open)
Abstract Objectives To identify and classify submucosal tumors by building and validating a radiomics model with gastrointestinal endoscopic ultrasonography (EUS) images. Methods A total of 144 patients diagnosed with submucosal tumors through gastrointestinal EUS were collected between January 2019 and October 2020. There are 1952 radiomic features extracted from each patient's EUS images. The statistical test and the customized least absolute shrinkage and selection operator regression were used for feature selection. Subsequently, an extremely randomized trees algorithm was utilized to construct a robust radiomics classification model specifically tailored for gastrointestinal EUS images. The performance of the model was measured by evaluating the area under the receiver operating characteristic curve. Results The radiomics model comprised 30 selected features that showed good discrimination performance in the validation cohorts. During validation, the area under the receiver operating characteristic curve was calculated as 0.9203 and the mean value after 10‐fold cross‐validation was 0.9260, indicating excellent stability and calibration. These results confirm the clinical utility of the model. Conclusions Utilizing the dataset provided curated from gastrointestinal EUS examinations at our collaborating hospital, we have developed a well‐performing radiomics model. It can be used for personalized and non‐invasive prediction of the type of submucosal tumors, providing physicians with aid for early treatment and management of tumor progression.